A characterization of intermediate‐scale spread F structure from four years of high‐resolution C/NOFS satellite data. Issue 6 (27th June 2016) - Rino, Charles L.; Carrano, Charles S.; Groves, Keith M.; Roddy, Patrick A.
Abstract: Power law spectra have been invoked to interpret equatorial scintillation data for decades. Published analyses of intensity and phase scintillation data typically report power law spectra of the form q − p with 2.4 < p < 2.6. However, in situ rocket and satellite measurements of equatorial spread F have shown evidence of spectra with two power law components. Strong scatter simulations and recent theoretical results have shown that two‐component power law spectra can reconcile simultaneous equatorial scintillation observations from VHF to S‐Band. The Communication/Navigation Outage Forecasting System (C/NOFS) satellite Planar Langmuir Probe generated a multiyear high‐resolution sampling of equatorial spread F, but published analyses to date have reported only single‐component power laws over scales from tens of kilometers to 70 m. This paper summarizes the analysis of high‐resolution C/NOFS data collected over the four year period 2011 to 2014. Following an earlier investigation of several months of C/NOFS data by the authors of this paper, the extended data set revealed a pattern of occurrence of two‐component spectra in the most highly disturbed data sets. The results confirm a known inverse correlation between turbulent strength and spectral index. The new results are interpreted as an equatorial spread F life cycle pattern with two‐component spectra in the early development phase giving way to single‐component spectra in the decay phase. Key Points: Power law classification of four years C/NOFS parallel Langmiur probe data Identification of recurrent power law structure change Association of two‐component power law with most highly disturbed data segments